Pencegahan dan Peningkatan Kesehatan Jiwa Remaja di Masa Pandemi Covid-19: Prevention and Improvement of Youth Mental Health During the Covid-19 Pandemic - Enjelita Mariance Ndoen; Theodora Takalapeta (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2023)
The Covid-19 pandemic has caused changes in activity patterns and life habits, which have an impact on increasing psychosocial pressure and psychological (mental) problems in adolescents, such as feelings of anxiety and loneliness, during the Covid-19 pandemic. Complaints about changes in behavior and emotions during the Covid-19 pandemic were also found in SMA Negeri 2 Kupang City students. Most students show feelings of boredom, irritability, lack of enthusiasm, and stress, as well as internet and online game dependency behavior. Students and teachers also lack knowledge about mental health and Covid-19 prevention behavior. This community service activity is carried out to increase the knowledge and abilities of students and teachers in recognizing and maintaining adolescent mental health while implementing appropriate preventive behavior during the Covid-19 pandemic. Service activities include counseling on mental health and the Covid-19 pandemic, social skills training (life skills), provision of IEC media in the form of youth mental health leaflets/posters during the Covid-19 pandemic, and provision of PHBS supporting facilities to implement the Covid-19 Pandemic behavior. The activity results showed that after counseling, there was an increase of 82.5% for students of SMAN 2 Kupang with a good level of knowledge. All students participating in community service activities can also practice skills in preventing and improving mental health and preventing the transmission of Covid-19. The school (students and teachers) should consistently educate youth mental health and health protocols to all students of SMAN 2 Kupang.